Carfilzomib, lenalidomide, and dexamethasone or lenalidomide alone as maintenance therapy after autologous stem-cell transplantation in patients with multiple myeloma (ATLAS): interim analysis of a randomised, open-label, phase 3 trial. Issue 2 (February 2023) - Dytfeld, Dominik; Wróbel, Tomasz; Jamroziak, Krzysztof; Kubicki, Tadeusz; Robak, Paweł; Walter-Croneck, Adam; Czyż, Jarosław; Tyczyńska, Agata; Druzd-Sitek, Agnieszka; Giannopoulos, Krzysztof; Nowicki, Adam; Szczepaniak, Tomasz; et al.
Summary: Background: Lenalidomide is a cornerstone of maintenance therapy in patients with newly diagnosed multiple myeloma after autologous stem-cell transplantation. We aimed to compare the efficacy and safety of maintenance therapy with carfilzomib, lenalidomide, and dexamethasone versus lenalidomide alone in this patient population. Methods: This study is an interim analysis of ATLAS, which is an investigator-initiated, multicentre, open-label, randomised, phase 3 trial in 12 academic and clinical centres in the USA and Poland. Participants were aged 18 years or older with newly diagnosed multiple myeloma, completed any type of induction and had stable disease or better, autologous stem-cell transplantation within 100 days, initiated induction 12 months before enrolment, and an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients were randomly assigned (1:1) using permuted blocks of sizes 4 and 6 and a web-based system to receive up to 36 cycles of carfilzomib, lenalidomide, and dexamethasone (28-day cycles of carfilzomib 20 mg/m 2 administered intravenously in cycle one on days 1 and 2 then 36 mg/m 2 on days 1, 2, 8, 9, 15, and 16 in cycles one to four and 36 mg/m 2 on days 1, 2, 15, and 16 from cycle five up to 36 [per protocol]; lenalidomide 25 mg administered orally on days 1–21; and dexamethasone 20 mg administered orally on days 1, 8, 15, and 22) or lenalidomide alone (10 mg administered orally for the first three cycles and then at the best tolerated dose [≤15 mg for 28 days in 28-day cycles]) until disease progression or unacceptable toxicity as maintenance therapy. After 36 cycles, patients in both treatment groups received lenalidomide maintenance. Randomisation was stratified by response to previous treatment, cytogenetic risk factors, and country. Investigators and patients were not masked to treatment allocation. Patients in the carfilzomib, lenalidomide, and dexamethasone group with no detectable minimal residual disease after cycle six (as per International Myeloma Working Group criteria) and standard-risk cytogenetics were switched to lenalidomide maintenance as of cycle nine. The primary endpoint was progression-free survival in the intention-to-treat population (defined as all randomly assigned patients). Safety was analysed in all randomly assigned patients who received at least one dose of study treatment. This unplanned interim analysis was triggered by the occurrence of 59 (61%) of the expected 96 events for the primary analysis and the results are considered preliminary. This trial is registered with ClinicalTrials.gov, NCT02659293 (active, not recruiting) and EudraCT, 2015–002380–42. Findings: Between June 10, 2016, and Oct 21, 2020, 180 patients were randomly assigned to receive either carfilzomib, lenalidomide, and dexamethasone (n=93) or lenalidomide alone (n=87; intention-to-treat population). The median age of patients was 59·0 years (IQR 49·0–63·0); 84 (47%) patients were female and 96 (53%) were male. With a median follow-up of 33·8 months (IQR 20·9–42·9), median progression-free survival was 59·1 months (95% CI 54·8–not estimable) in the carfilzomib, lenalidomide, and dexamethasone group versus 41·4 months (33·2–65·4) in the lenalidomide group (hazard ratio 0·51 [95% CI 0·31–0·86]; p=0·012). The most common grade 3 and 4 adverse events were neutropenia (44 [48%] in the carfilzomib, lenalidomide, and dexamethasone group vs 52 [60%] in the lenalidomide group), thrombocytopenia (12 [13%] vs six [7%]), and lower respiratory tract infections (seven [8%] vs one [1%]). Serious adverse events were reported in 28 (30%) patients in the carfilzomib, lenalidomide, and dexamethasone group and 19 (22%) in the lenalidomide group. One treatment-related adverse event led to death (respiratory failure due to severe pneumonia) in the carfilzomib, lenalidomide, and dexamethasone group. Interpretation: This interim analysis provides support for considering carfilzomib, lenalidomide, and dexamethasone therapy in patients with newly diagnosed multiple myeloma who completed any induction regimen followed by autologous stem-cell transplantation, which requires confirmation after longer follow-up of this ongoing phase 3 trial. Funding: Amgen and Celgene (Bristol Myers Squibb).